The Influence of Interior Design and Food Taste on Visitor Loyalty at Godong Ijo Sundanese Restaurants and Fishing - Siti Choerunisa; Rizki Nurul Nugraha (West Science Interdisciplinary Studies, 2024)
This research aims to determine the influence of interior design and food taste on visitor loyalty at Sundanese Resto & Fishing Godong Ijo. The population of this study were all tourists who had visited the Sunda Resto & Fishing Godong Ijo with a sample of 120 people. This research uses primary data obtained through distributing questionnaires and interviews. The analysis technique used is the Partial Least Square (PLS) approach method which utilizes PLS-SEM or Structural Equation Modeling to measure and analyze the relationship between variables. From data processing using SmartPLS 4, Interior Design variables influence Customer Loyalty and the Food Taste variable influences Customer Loyalty.